FENOMENOLOGI LOOKISM PADA MASYARAKAT PENGGUNA MEDIA SOSIAL TWITTER - Anisya Lutfia K Putri (2021)
Discussing social issues through social media on twitter has become commonplace, as one has emerged from the lookism phenomenon in society. The lookism phenomenon is viral and is being hot topic. The lookism phenomenon was first discussed via social media on twitter in differences in treatment of the drug case Jefri Nichol dan Ibnu Rahim, or in Zara's (ex-JKT48) case and Youtuber Kekeyi. The lookism phenomenon has caused many people to speak for the effect of that. They share their opinions and experiences as people who unqualified the beauty standards. Based on the experience they share, many talk about preferential treatment received by a person with a good appearance. That's because physical attractiveness is the most attention given in the research on facial impressions, it was called 'attractiviness hello', that is, people with attractive faces are more positive and accompanied by preferential treatment (Zebrowitz, 2008). This study uses qualitative method with phenomenologyl approach to examine the lookism phenomenon based on the experiences of people who used Twitter. The research data were obtained through observation and deep interviews conducted on seven twitter users have had an experience with the lookism phenomenon. The research findings showed that the phenomenon of lookism has resulted in discrimination of the appearance felt by people who unqualified the beauty standards called "no good looking". It refers to social and occupational aspects that cause psychological and social impact. That discrimination referring to the social and occupational aspects that cause psychological and social impact. Psychologically impact based on statements from the informants caused a low level of confidence, developed self-esteem (insecure), made self blaming and trauma. And the social impact of affecting the reduced social social networks.